Indirect contagion: the policy problem - Laurent Clerc; Alberto Giovannini; Sam Langfield; Tuomas Peltonen; Richard Portes; Martin Scheicher (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
An epidemiologist calculating the risk of a localised epidemic becoming a global pandemic would investigate every possible channel of contagion from the infected region to the rest of the world. Focusing on, say, the incidence of close human contact would underestimate the pandemic risk if the disease could also spread through the air. Likewise, calculating the quantity of financial system risk requires practitioners to understand all of the channels through which small and local shocks can become big and global. Much of the empirical finance literature has focused only on "direct" contagion arising from firms' contractual obligations. Direct contagion occurs if one firm's default on its contractual obligations triggers distress (such as illiquidity or insolvency) at a counterparty firm. But contractual obligations are not the only means by which financial distress can spread, just as close human contact is not the only way that many infectious diseases are transmitted. Focusing only on direct contagion underestimates the risk of financial crisis given that other important channels exist. This paper represents an attempt to move systemic risk analysis closer to the holism of epidemiology. In doing so, we begin by identifying the fundamental channels of indirect contagion, which manifest even in the absence of direct contractual links. The first is the market price channel, in which scarce funding liquidity and low market liquidity reinforce each other, generating a vicious spiral. The second is information spillovers, in which bad news can adversely affect a broad range of financial firms and markets. Indirect contagion spreads market failure through these two channels. In the case of illiquidity spirals, firms do not internalise the negative externality of holding low levels of funding liquidity or of fire-selling assets into a thin market. Lack of information and information asymmetries can cause markets to unravel, even following a relatively small piece of bad news. In both cases, market players act in ways that are privately optimal but socially harmful. The spreading of market failure by indirect contagion motivates policy intervention. Substantial progress has been made in legislating for policies that will improve systemic resilience to indirect contagion. But more tools might be needed to achieve a fully effective and efficient macroprudential policy framework. This paper aims to frame a high-level policy discussion on three policy tools that could be effective and efficient in ensuring systemic resilience to indirect contagion - namely macroprudential liquidity regulation; restrictions on margins and haircuts; and information disclosure.
Keywords: G15; G18; 330; contagion; systemic risk; financial distress; liquidity shortages